169k views
22 votes
Part one is -3 and 7
part two is -3

Part one is -3 and 7 part two is -3-example-1
User Pauby
by
6.4k points

1 Answer

7 votes

Answer:

Given equation:


√(30-2x) =x-3

Square both sides:


\implies (√(30-2x))^2 =(x-3)^2


\implies 30-2x =(x-3)^2

Expand the right side:


\implies 30-2x =x^2-6x+9

Add
2x to both sides:


\implies 30 =x^2-4x+9

Subtract 30 from both sides:


\implies x^2-4x-21=0

Factor:


\implies (x-7)(x+3)=0

Therefore,


x-7=0 \implies x =7


x+3=0 \implies x=-3

Substitute both values of
x into the original equation to check:


x=7 :


\implies√(30-2(7)) =7-3


\implies 4=4

correct!


x=-3


\implies√(30-2(-3)) =-3-3


\implies 6 \\eq =-6

incorrect!

Therefore,
x=7 is the only correct solution, and
x=-3 is the extraneous solution

**Extraneous solution: a root of a transformed equation that is not a root of the original equation**

User Tomasz Kaniewski
by
5.9k points